If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15t + -9 + -8t = 5 Reorder the terms: -9 + 15t + -8t = 5 Combine like terms: 15t + -8t = 7t -9 + 7t = 5 Solving -9 + 7t = 5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 7t = 5 + 9 Combine like terms: -9 + 9 = 0 0 + 7t = 5 + 9 7t = 5 + 9 Combine like terms: 5 + 9 = 14 7t = 14 Divide each side by '7'. t = 2 Simplifying t = 2
| x+.40=168 | | 5/6h-3/4h=-13/6+2/12 | | 0.4x-0.3(30+x)=-0.2(30) | | -2(4x+9)=-8x-18 | | 8.77xy=8.00 | | x+7x-8=8 | | (3x-9)(x+4)=0 | | 4y+228=52 | | 12a-24=12 | | 3x+4(x+3)=68 | | 3x-8+x+12=17 | | -15*5/3c*8 | | -5(2x-1)=3(x+5) | | 56y+1=781 | | 6x+8=290 | | -3+1=x+9-4x | | v/4-10=5 | | 1.5x-18=0.5x | | 22/11x9-3 | | -4/3+x2+1/3x-8+8/3x | | 5v^2=20 | | 2/63/6= | | (2r-4s+6t)(2r-4s+6t)= | | 5y+y-9=8y+1 | | 4+12/4-2 | | 80x^2=50 | | 3(a-5)=6a(3a+15) | | -4/3+t2+1/3t-8+8/3t | | (a/6)-11=25 | | (3xy^2)(-5x^3y)= | | 4x-25x^1/2+25=0 | | 8x-36=8 |